Dissociation and Self-Preservation of Gas Hydrates in Permafrost - Evgeny Chuvilin; Boris Bukhanov; Dinara Davletshina; Sergey Grebenkin; Vladimir Istomin (Geosciences, 2018)
Gases releasing from shallow permafrost above 150 m may contain methane produced by the dissociation of pore metastable gas hydrates, which can exist in permafrost due to self-preservation. In this study, special experiments were conducted to study the self-preservation kinetics. For this, sandy samples from gas-bearing permafrost horizons in West Siberia were first saturated with methane hydrate and frozen and then exposed to gas pressure drop below the triple-phase equilibrium in the “gas–gas hydrate–ice” system. The experimental results showed that methane hydrate could survive for a long time in frozen soils at temperatures of −5 to −7 °C at below-equilibrium pressures, thus evidencing the self-preservation effect. The self-preservation of gas hydrates in permafrost depends on its temperature, salinity, ice content, and gas pressure. Prolonged preservation of metastable relict hydrates is possible in ice-rich sandy permafrost at −4 to −5 °C or colder, with a salinity of <0.1% at depths below 20–30 m.